-3x-1-5x+4=

Simple and best practice solution for -3x-1-5x+4= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-1-5x+4= equation:


Simplifying
-3x + -1 + -5x + 4 = 0

Reorder the terms:
-1 + 4 + -3x + -5x = 0

Combine like terms: -1 + 4 = 3
3 + -3x + -5x = 0

Combine like terms: -3x + -5x = -8x
3 + -8x = 0

Solving
3 + -8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3' to each side of the equation.
3 + -3 + -8x = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -8x = 0 + -3
-8x = 0 + -3

Combine like terms: 0 + -3 = -3
-8x = -3

Divide each side by '-8'.
x = 0.375

Simplifying
x = 0.375

See similar equations:

| t^2=3t+7 | | 9-7x=108-28x | | 9-2x=x | | 6+5x=x | | x-2(x-1)=4-3(x-2) | | 13-8z=7 | | 12+5=11+12x | | -3(x-7)+2= | | 9(2-a)=63 | | 3(2+5m)=-54 | | 17(x-2)=34 | | 17(x-2)= | | 10-2(x+3)=3+3(2x+5) | | 4b-(9b-8)= | | 3x^2+10x+5=0 | | 379.94=3.14*r^2 | | 4+45=8x+13 | | 2x-5x=x+8 | | 4x+10=2x+29 | | -7y-(2y+4)= | | 4x^2+13=3 | | 2x^2=162 | | 5-4(x+1)=4x-3(4x-1)-4 | | 9+3b=18 | | 9+3b=15 | | 75.36=2r*3.14 | | 5m=10-5m | | 3(x+15)+4(9-x)=0 | | 8r=-4r-12 | | x^2-6=55 | | 0.2x+9=8(0.4x-1) | | -2=3n+6-5n |

Equations solver categories